SELF-CONCEALMENT IN INDIVIDUALS WHO ENDURED TRAUMATIC EVENTS: WHY EMOTION REGULATION IS NECESSARY? - Amalia Juniarly; Kgs. Muhammad Akbar Hakim; Rachmawati; Tarigan, Angeline Hosana Zefany; Dewi Anggraini (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
Traumatic experiences often have long-term effects on an individual's psychological well-being. When individuals choose to conceal or suppress information related to their trauma, it can worsen their mental health condition. This study aims to examine the relationship between self-concealment tendencies and emotion regulation abilities among individuals who have experienced traumatic events. A quantitative approach was employe using incidental sampling technique. The study involved 177 participants, with an additional 50 participants included for instrument try-out. The instruments used consisted of a self-concealment scale based on Larson's (1990) theory and an emotion regulation scale based on Gross's (2007) theory. Data were analyzed using Pearson's Product Moment correlation, yielding a correlation coefficient (r) of -0.164, with a significance level of 0.029 (p<0.05). The findings indicate a significant negative correlation between self-concealment and emotional regulation. In other words, individuals with better emotional regulation are more likely to engage less in self-concealment and vice versa. Adaptive emotional regulation strategies, such as emotional disclosure, are recommended to reduce tendencies toward self-concealment and enhance emotional well-being.